(untitled) (Journal of Foreign Language Studies, 2024)
Advertising has been creeping into people’s lives and affecting their behaviors. One of the effective strategies to attract customers is to incorporate cultural elements in advertising. This study focuses on examining creative tactics for expressing individualist and collectivist values to point out the similarities and differences in the representation of these values. A cross-cultural comparative method based on the content analysis approach was employed to analyze two datasets, including 131 selected American and 123 selected Vietnamese magazine advertisements. The results show that creative tactics for individualist values are found more in American advertisements, while those for collectivist values are used more in Vietnamese advertisements. This study has both academic and practical implications, helping advertisers have a more objective view of the outstanding advertising tactics in each data set, thereby creating more appropriate advertisements for their target customers.